Emotion Suppression and Aggressive Behavior: Frustration Tolerance as a Mediator in Young Adults - Ben Amor, Leila; Mchedlidze, Nino (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the mediating role of frustration tolerance in the relationship between emotion suppression and aggressive behavior among young adults. Methods and Materials: A descriptive correlational research design was employed with a sample of 400 young adults aged 18–30 from Georgia, selected based on the Morgan and Krejcie sample size table. Participants completed standardized self-report instruments: the Emotion Regulation Questionnaire (Suppression Subscale), the Frustration Discomfort Scale, and the Buss–Perry Aggression Questionnaire. Data were analyzed using SPSS-27 for descriptive and Pearson correlation analyses, and AMOS-21 for structural equation modeling (SEM). Assumptions for normality, linearity, and multicollinearity were confirmed prior to model testing. Findings: Emotion suppression was significantly and negatively correlated with frustration tolerance (r = −.43, p < .001) and positively correlated with aggressive behavior (r = .48, p < .001). Frustration tolerance was also negatively correlated with aggressive behavior (r = −.52, p < .001). SEM results indicated good model fit (χ²/df = 2.22; CFI = 0.96; RMSEA = 0.056). Emotion suppression had a significant direct effect on aggression (β = 0.29, p < .001), as well as an indirect effect via frustration tolerance (β = 0.21, p < .001), confirming partial mediation. The total effect of emotion suppression on aggressive behavior was strong (β = 0.50, p < .001). Conclusion: The findings suggest that frustration tolerance partially mediates the relationship between emotion suppression and aggressive behavior in young adults. Individuals who suppress their emotions tend to exhibit lower frustration tolerance, which increases their likelihood of aggressive responses. Interventions aimed at enhancing emotional expression and frustration management may reduce aggression in this population.